Two new species from South Africa, with remarks on generic diagnosis of Licnodamaeolus Covarrubias, 1998 and taxonomic status of Nacunansella Fernandez & Cleva, 1998 (Acari: Oribatida: Licnodamaeidae) - Ermilov, Sergey G.; Hugo-Coetzee, Elizabeth A. (Zootaxa, 2012)
Two new species of oribatid mites of the family Licnodamaeidae, Licnodamaeolus asetosus sp. nov. and L. erfenisdamen-sis sp. nov., are described from clay soil in grassland vegetation in Erfenis Dam Nature Reserve (central South Africa).These represent the first finding of Licnodamaeolus Covarrubias, 1998 in the African continent. Nacunansella Fernandez& Cleva, 1998 is recognized as a junior synonym of Licnodamaeolus. A new generic diagnosis of Licnodamaeolus is presented. A comparative analysis of all known species of Licnodamaeolus is given.